2009
DOI: 10.1111/j.1365-2230.2009.03208.x
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte cytogenetics in 10 patients with pigmentary mosaicism: identification of one case of trisomy 20 mosaicism confined to keratinocytes

Abstract: In patients with clinically suspected PM but normal blood cytogenetics, keratinocytes may be more sensitive than skin fibroblasts in identifying cytogenetic mosaicism in selected patients. However, the additional diagnostic yield appears to be insufficient to justify routine keratinocyte cytogenetic investigation. Our findings indirectly support the hypothesis that Blaschko's lines delineate the embryonal migration paths taken by ectodermal cells including keratinocytes and melanocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 18 publications
0
8
0
12
Order By: Relevance
“…Studies of large populations of patients with idiopathic mental retardation and normal karyotype by conventional testing have found chromosome abnormalities in up to 17% of cases when genome-wide microarray platforms are used [12]. More graphic examples of human tissue mosaicism can be found in two disorders of cutaneous pigmentation: hypomelanosis of Ito and linear and whorled hypermelanosis [13]. The pigmentary patterns in these disorders follow Blaschko's lines which are believed to trace the migration of embryonic cells.…”
Section: Discussionmentioning
confidence: 96%
“…Studies of large populations of patients with idiopathic mental retardation and normal karyotype by conventional testing have found chromosome abnormalities in up to 17% of cases when genome-wide microarray platforms are used [12]. More graphic examples of human tissue mosaicism can be found in two disorders of cutaneous pigmentation: hypomelanosis of Ito and linear and whorled hypermelanosis [13]. The pigmentary patterns in these disorders follow Blaschko's lines which are believed to trace the migration of embryonic cells.…”
Section: Discussionmentioning
confidence: 96%
“…Some studies have demonstrated cytogenetic abnormalities in keratinocyte and melanocytes cultures. [12] Management of pigment mosaicism is multidisciplinary and mainly depends on the underlying systemic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Such discordance between karyotypes of blood and skin is rare but has been reported. 4 Skin pigmentation is closely related to epidermal-dermal interaction. Although pigmentation is primarily related to the melanocytes, the surrounding keratinocytes and extracellular matrix proteins and fibroblasts in the underlying dermal compartments actively contribute to cutaneous homeostasis.…”
mentioning
confidence: 99%